New imaging findings of tumor invasion into brain tissue: “Peritumoral Hyperintense Enhancement Sign” - Mao, Xinyi; Li, Jianye; Zheng, Xuejun; Wang, Yujun; Gao, Jie; Fu, Chunlong; Li, Xin; Liang, Ming; Wang, Xiangping; Qiu, Tiantian; Du, Haijun; Xue, Chen; et al. (Frontiers in Human Neuroscience, 2025)
IntroductionThis study investigated the MRI characteristics of meningiomas and brain metastases, exploring the relationship between the “Peritumoral Hyperintense Enhancement Sign” and brain invasion, and its clinical implications for treatment planning.MethodsA multicenter retrospective analysis was conducted on 24 cases (17 brain metastases and 7 meningiomas), examining the MRI features of the “Peritumoral Hyperintense Enhancement Sign” and corresponding histopathological characteristics.ResultsAll cases demonstrated peritumoral enhancement: 8 cases exhibited flame-shaped enhancement, 12 showed crescentic enhancement, and 4 displayed both patterns. Histopathological analysis confirmed brain invasion in regions showing abnormal enhancement.ConclusionThe “Peritumoral Hyperintense Enhancement Sign” not only serves as a valuable indicator of brain invasion and provides guidance for clinical target delineation in treatment planning, but also facilitates more precise treatment planning and may contribute to improved prognostic assessment and reduced recurrence risk.